The Sampling Distribution of Sample Means - Subedi, Shantiram (Damak Campus Journal, 2023)
This article explains what sampling distribution is, how you can use it and the factors that influence its calculation, and the types of sampling and types of sampling distribution. We further define variance, describe how to calculate it and explain the advantages and disadvantages of using a variance.